IMPLEMENTASI KURIKULUM MERDEKA DI SDN SUNGAI LULUT 7: KENDALA GURU DALAM PEMBELAJARAN DAN SISWA DALAM ASESMEN PEMBELAJARAN - Hutri Hidayah; Najma Soraya; Nova Soraya; Siti Munawarah; Diani Ayu Pratiwi; Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the implementation of the Kurikulum Merdeka and various challenges faced by teachers and students in the teaching and learning process as well as in conducting assessments. Teachers encounter obstacles in adapting instructional strategies to meet students’ needs, especially in selecting appropriate learning materials and fostering an effective learning environment. Meanwhile, students face issues such as anxiety, poor time management, and low motivation in understanding the subject matter. These challenges directly impact their assessment performance. Therefore, it is essential for teachers to apply interactive and adaptive learning methods and provide emotional support to boost students' confidence. This study offers an overview of how pedagogical and psychological factors interact to influence the success of assessments in the context of the Kurikulum Merdeka.